2009
DOI: 10.5194/hess-13-793-2009
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of potential vorticity uncertainties into a hydrometeorological forecasting chain: application to a medium size basin of Mediterranean Spain

Abstract: Abstract. The improvement of the short-and mid-range numerical runoff forecasts over the flood-prone Spanish Mediterranean area is a challenging issue. This work analyses four intense precipitation events which produced floods of different magnitude over the Llobregat river basin, a medium size catchment located in Catalonia, north-eastern Spain. One of them was a devasting flash flood -known as the "Montserrat" event -which produced 5 fatalities and material losses estimated at about 65 million euros. The cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…For example, Amengual et al . () found that two of the most catastrophic extreme floods during the last 50 years in the Llobregat catchment occurred in November 1996 and December 1997. In contrast, in 2005, Spain, Portugal and France experienced an extreme drought with the lowest annual precipitation recorded since 1947.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Amengual et al . () found that two of the most catastrophic extreme floods during the last 50 years in the Llobregat catchment occurred in November 1996 and December 1997. In contrast, in 2005, Spain, Portugal and France experienced an extreme drought with the lowest annual precipitation recorded since 1947.…”
Section: Discussionmentioning
confidence: 99%
“…The extreme flood and drought periods observed in our study also correspond with what is known for the region: floods were more common at the beginning of the series and droughts more common at the end. For example, Amengual et al (2009) found that two of the most catastrophic extreme floods during the last 50 years in the Llobregat catchment occurred in November 1996 and December 1997. In contrast, in 2005, Spain, Portugal and France experienced an extreme drought with the lowest annual precipitation recorded since 1947.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show the promise of adopting streamflow ensemble forecast techniques due to advantages over deterministic forecasts (Habets et al, 2004;Younis et al, 2008;Boucher et al, 2011;Schellekens et al, 2011;Verkade and Werner, 2011;Alfieri et al, 2013) as well as a way of accounting for uncertainties in hydrological forecasting (Chen and Yu, 2007;Demeritt et al, 2007;Davolio et al, 2008;Pappenberger et al, 2008;Reggiani and Weerts, 2008;Cloke and Pappenberger, 2009;Bao et al, 2011;Bogner and Pappenberger, 2011;Cuo et al, 2011;Schellekens et al, 2011;Alfieri et al, 2012;Amengual et al, 2015). Other advantages include the ability to distinguish between an extreme event forecast that is more or less likely to occur within the model's forecast horizon (Buizza, 2008;Golding, 2009) and better decision making with respect to operational hydrological concerns (Ramos et al, 2007;McCollor and Stull, 2008;Boucher et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of international efforts in this field are [2,[5][6][7][8]. [5] presented a forecasting approach of the potential for flash flood producing storms using the notion of basic ingredients.…”
Section: Introductionmentioning
confidence: 99%